Housing conditions and risk of incident COPD: a Danish cohort study, 2000-2018 - Stine Kloster; Anne Marie Kirkegaard; Michael Davidsen; Anne Illemann Christensen; Niss Skov Nielsen; Lars Gunnarsen; Jørgen Vestbo; Annette Kjær Ersbøll (BMC, 2024)
Abstract Background More knowledge is needed on the risk of developing chronic obstructive pulmonary disease (COPD) associated with housing conditions and indoor environment based on cohort studies with a long follow-up time. Objective To examine the association between housing conditions and indoor environment and the risk of developing COPD. Methods In this cohort study, we followed 11,590 individuals aged ≥ 30 years free of COPD at baseline. Information on incident COPD and housing conditions and indoor environment was obtained from the Danish national registers and the Danish Health and Morbidity Survey year 2000. Poisson regression of incidence rates (IRs) were used to estimate incidence rate ratios (IRRs) of COPD. Results The overall IR of COPD was 8.6 per 1,000 person-years. Individuals living outside the biggest cities vs. living in the biggest cities (≥ 50,000) had a lower risk of COPD (200-4,999; IRR 0.77 (95% CI 0.65-0.90). Individuals living in semi-detached houses had a higher risk compared to individuals living in detached houses (IRR 1.29 (95% CI 1.07-1.55)). Likewise, individuals living in rented homes had a higher risk (IRR 1.47 (95% CI 1.27-1.70)) compared to individuals living in owned homes. The IR of COPD was 17% higher among individuals living in dwellings build > 1982 compared with individuals living in older dwellings (< 1962), not statistically significant though (IRR 0.83 (95% CI 0.68-1.03)). Likewise, the IR of COPD was 15% higher among individuals living in the densest households compared with individuals living in the least dense households, not statistically significant though (IRR 1.15 (95% CI 0.92-1.45)). This was primary seen among smokers. There was no difference in risk among individuals with different perceived indoor environments. Overall, similar patterns were seen when stratified by smoking status with exception of perceived indoor environment, where opposite patterns were seen for smokers and never smokers. Conclusion Individuals living in semi-detached houses or rented homes had a higher risk of developing COPD compared to individuals living in detached or owned homes. Individuals living in cities with < 50.000 residents had a lower risk of COPD compared to individuals living in cities with ≥ 50.000 residents.